A new species of the genus Genusa (Lepidoptera, Geometridae, Ennominae) from China - Cui, Le; Xue, Dayong; Zhang, Chuntian; Han, Hongxiang (Zootaxa, 2014)
Genusa Walker, 1855, a genus currently included in the Hypochrosini, was originally established in the Lymantriidae, and transferred to the Geometridae by Hampson (1895), who designated G. bigutta Walker, 1855 as the type species, and listed G. destituta Walker, 1865, originally described from Cambodia, as a synonym of G. bigutta, though without any explanation. The only literature which compared destituta with bigutta is Swinhoe (1900), where he stated that destituta is hardly separable from G. bigutta.